Pengembangan media pembelajaran berbasis PowerPoint interaktif pembelajaran sains di kelas III sekolah dasar (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
The aim of this research is to develop interactive powerpoints as learning media in Natural Sciences subjects using the application of the development model according to Sukmadinata, there are three stages, namely preliminary studies, product development and product testing, where at the stages in product development apply the ADDIE learning model which stands for Analysis, Design , Development, Implementation and Evaluation, on the implementation of the process of making media or the products produced. Next, find out whether an interactive powerpoint product that has been developed is suitable for use in learning Natural Sciences and its effect on student activity and motivation. From the research conducted, the feasibility level of the media using Microsoft PowerPoint is in the feasible category.